2019
DOI: 10.1016/j.eplepsyres.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous brivaracetam in status epilepticus: Correlation between loading dose, plasma levels and clinical response

Abstract: Brivaracetam is available in intravenous formulation, and its favourable pharmacokinetic profile makes it a promising agent in the treatment of status epilepticus (SE). Its availability as an intravenous formulation and its favourable pharmacokinetic profile make it a promising agent in the treatment of status epilepticus. Our aim was to assess the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 19 publications
2
31
1
Order By: Relevance
“…At >50%, the effectiveness rate is similar to that published by Kalss et al (seven patients; 57%) and Aicua‐Rapun et al (14 patients; 50%); compared with the Strzelczyk cohort (11 patients; 27%), the response rate of our sample is higher, although in his series only refractory and superrefractory cases were reported and BRV was administered later.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…At >50%, the effectiveness rate is similar to that published by Kalss et al (seven patients; 57%) and Aicua‐Rapun et al (14 patients; 50%); compared with the Strzelczyk cohort (11 patients; 27%), the response rate of our sample is higher, although in his series only refractory and superrefractory cases were reported and BRV was administered later.…”
Section: Discussionsupporting
confidence: 89%
“…Effectiveness in SE in the context of IGE was also found; of the five patients with previous IGE diagnosis, three had a fast clinical and EEG response, with this occurring within 10‐20 minutes in two of them. The only published information on BRV used for SE in IGE patients is the two cases reported by Strzelczyk et al of SE with absences, which had no response . In our cases, the three IGE responder patients were already on treatment with BRV, the cause of their SE was abrupt drug withdrawal (forgot medication), and all three had a predominantly myoclonic component (two previous diagnoses of JME and one of Jeavons syndrome); the two nonresponders were SE with absences with no myoclonic component.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Despite neither BRV nor LEV being indicated for SE, recent studies have suggested that SE patients can be treated with BRV, with loading doses similar to those in this study . A further recent study has reported that a human dose of at least 2 mg/kg and up to 5 mg/kg is necessary for efficacy in SE, suggesting that doses slightly above 100 mg BRV intravenously could be in the efficacious range . The tracer displacement half‐time is an underestimation of the drug brain entry half‐time, because of the time taken for tracer clearance from tissue.…”
Section: Discussionmentioning
confidence: 57%
“…(mRS) scores at admission and discharge, and in responders and nonresponders to topiramate (TPM) [41][42][43] Two recent case series reported on the use of oral perampanel in patients with various stages of SE, reporting response rates between 17% 44 and 37%. 45 Use of oral oxcarbazepine in SE was reported in 13 patients with a median treatment latency of 81 hours.…”
Section: F I G U R E 2 Modified Rankin Scalementioning
confidence: 99%